Technologies shaping instruction and distance education : new studies and utilizations - Syed, Mahbubur Rahman, 1952- (Hershey, PA : Information Science Reference, 2010)
'This book covers the use of technology and the development of tools to support content exchange, delivery, collaboration and pedagogy used in distance education delivery'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Distance education -- Computer-assisted instruction; Education -- Effect of technological innovations on; Educational technology